Study on Heat Dissipation of Reduction Gearbox of a Hoisting Mechanism in Stopped State - Gao Chunhui; Hu Xiong (Jixie chuandong)
The shore bridge reducer in the lifting mechanism often emit heat because of continuous operation and high load,if improper heat dissipation will greatly reduce its life. To achieve the real-time online condition assessment of the reduction gearbox of the hoisting mechanism,the influence parameters of heat dissipation should be known for determining the heat dissipation condition. In order to obtain the influence parameters,from the simplest condition,the stopped state in the work,by using the lumped heat capacity method,the reduction gearbox heat dissipation model is studied,the curve fitting theoretic support and the factors that can affect the heat dissipation are got. In order to verify the actual influence of these factors on the reducer heat dissipation,by using the control variable method,the actual temperature data is computed and analyzed. Then,by means of the function mapping software Origin,the temperature data of the reduction gearbox is fitted,a quadratic exponential function model is fitted and the function parameter is obtained. Combining with the influence factors,the regularity analysis is carried out,the foundation for future work of heat dissipation factor parametric is provided.